Mengintegrasikan Etika Kristen Dan Moderasi Beragama Dalam Pembelajaran PAK Untuk Menciptakan Generasi Toleran di GBI Cilamaya Karawang Jawa Barat - Heru Cahyono; Suhartono, Tony; Suriyanti, Intan; Setiawan, Eko Agus (JURNAL TABGHA, 2025)
Facing the complex diversity in Indonesia, enhancing interfaith tolerance is a significant challenge, especially among the younger generation. This study aims to evaluate the effects of integrating Christian ethics and religious moderation into Christian Religious Education (CRE) at Bethel Church Indonesia (GBI) Cilamaya, Karawang, West Java. The study involved 82 junior and senior high school students participating in a learning program designed to enhance tolerance through understanding the values of other religions and positive intergroup interactions. The methods used were pre and post-intervention surveys, along with classroom interaction observations to document changes in attitudes towards tolerance and cooperation among students from various religious backgrounds. The results show that after the program, 75% of students demonstrated increased understanding of other religious values, and observations revealed significant enhancements in group discussions and more inclusive social interactions. This research indicates that the integration of Christian ethics and religious moderation effectively fosters tolerance among students, suggesting that such an approach can contribute significantly to preparing the younger generation to live in a harmonious multicultural society.